The genesis of the sports clubs movement in Poland - Piotr Kędzia (Kazimierz Wielki University, 2020)
The formation of the first Polish sports associations is not only an important stage in the development of Polish sport, but is also a crucial element of Polish tradition and culture. The process of shaping the sports association movement, initiated in the 19th century, was a reflection of the social, political and economic changes that took place throughout Europe, including the Polish lands under partitions. It is the sports associations that are the keystone of various activities that have introduced to social life such phenomena as mass and competitive sport, a sports spectacle, the principle of fair play, the fan movement and others. Analyzing the course of formation of sports associations, Maria Rotkiewicz and Kajetan Hądzelek note: "Two stages can be distinguished in the development of Polish sport up to a year 1918: 1) the creation of sports associations in the second half of the nineteenth century, based on organizational models of aristocratic hippic and hunting societies; 2) development of the club movement in the first years of the twentieth century in Galicia, the Kingdom of Poland and Greater Poland, gathering primarily school and academic youth" [13, p. 130].